2011
DOI: 10.3390/toxins3121484
|View full text |Cite
|
Sign up to set email alerts
|

Trichothecene Mycotoxins Inhibit Mitochondrial Translation—Implication for the Mechanism of Toxicity

Abstract: Fusarium head blight (FHB) reduces crop yield and results in contamination of grains with trichothecene mycotoxins. We previously showed that mitochondria play a critical role in the toxicity of a type B trichothecene. Here, we investigated the direct effects of type A and type B trichothecenes on mitochondrial translation and membrane integrity in Saccharomyces cerevisiae. Sensitivity to trichothecenes increased when functional mitochondria were required for growth, and trichothecenes inhibited mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…These results reveal a previously unidentified mechanism against trichothecenes. media (0.75 μM) (12,13). Analysis of the identified strains revealed a vital role for mitochondrial oxidative stress in trichothecene sensitivity and provided the first evidence to our knowledge for a prosurvival role for the autophagic degradation of damaged mitochondria or mitophagy in the reduction of trichothecene-mediated mitochondrial oxidative stress.…”
Section: Significancementioning
confidence: 87%
See 3 more Smart Citations
“…These results reveal a previously unidentified mechanism against trichothecenes. media (0.75 μM) (12,13). Analysis of the identified strains revealed a vital role for mitochondrial oxidative stress in trichothecene sensitivity and provided the first evidence to our knowledge for a prosurvival role for the autophagic degradation of damaged mitochondria or mitophagy in the reduction of trichothecene-mediated mitochondrial oxidative stress.…”
Section: Significancementioning
confidence: 87%
“…2B) dropped at 6 h, possibly due to depolarization of the mitochondrial membrane (13). The decrease in mitochondrial membrane potential (13) may ultimately lead to further damage to mitochondria and other cellular functions and to eventual cell death.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These effects are mediated by interaction of DON with the ribosome and phosphorylation of ribosome associated mitogen-associated protein kinases (MAPK), which trigger immune responses including programmed cell death (Bae et al, 2010;Bae and Pestka, 2008;Zhou, 2003). However, the afore mentioned inhibition of cytosolic translation may not be the main cause of DON toxicity as recent studies in yeast showed that DON directly inhibits mitochondrial translation and that yeast cells lacking normal functioning mitochondria were resistant to otherwise lethal doses of DON (Bin-Umer et al, 2011McLaughlin et al, 2009). …”
Section: Don Inhibits Cytosolic As Well As Mitochondrial Protein Biosmentioning
confidence: 99%